Validity and Reliability Test of Teaching Materials Using Aiken's V Formula and SPSS 22 - Hidayah, Nur; Muhtarom (Universitas PGRI Semarang, 2023)
Based on the results of PISA in 2018, Indonesia experienced a decline compared to PISA in 2015. The low ability to solve problems was caused by several factors, one of which was the learning process carried out in schools. Problem solving used in learning makes students construct their knowledge and take a role in acquiring knowledge. Researchers will develop contextual learning-based teaching materials to improve problem solving skills in grade V elementary school science students by validating the items on the instrument for preparing teaching materials. This research uses a quantitative approach, in the form of statistical data. The calculation process in determining the validity of the instrument uses Aiken's V and to test the reliability of teaching materials using SPSS 22. The research was carried out by distributing validation questionnaires for teaching materials to 5 validators as respondents. Based on the results of the content validation test analysis taking into account the categorization determination values shown in the Aiken's V Table with a coefficient value of 0.87 showing at 0.95. Meanwhile, the data reliability results show that r = 0.902 with r table 0.878. These teaching materials are declared valid and reliable so they are suitable for use.